CLINICAL STAGE OF ORAL CANCER PATIENTS AT THE TIME OF INITIAL DIAGNOSIS - Shah, Irfan; Sefvan, Omer; Luqman, Uzair; Ibrahim, Waseem; Mehmood, Sana; Alamgir, Wajiha (Journal of Ayub Medical College Abbottabad, 2010)
Background: Squamous cell carcinoma is the most common oral cancer. Early diagnosis ensures better prognosis. Late diagnosis is however common around the world and contributes to the high morbidity and mortality related to oral cancer. The objective of this study was to determine the clinical stage of oral cancer patients at the time of diagnosis. Methods: This retrospective study was carried out on 334 oral cancer patients who presented to the outdoor departments of Armed Forces Institute of Dentistry, and Armed Forces Institute of Pathology, Rawalpindi from July 2008 to December 2009. The records that were reviewed included history and clinical examination findings, OPG and CT scans of the head and neck region, chest X-rays, abdominal ultrasounds and liver function tests. Size of the primary tumour, the size, number and laterality of the involved cervical lymph nodes and the presence/absence of distant metastases were documented and statistically analysed using SPSS-17. Results: Out of the 334 patients, 203 (60.8%) were males and 131 (39.2%) females. The age range was from 21 to 88 years. Buccal mucosa was the most commonly involved site (32 %). The primary tumour was 4 Cm or more in size, (T3/T4) 71.25% of the cases. Cervical lymph nodes were involved in 211 patients (63.2%) and distant metastases were present in 39 patients (11.7%). Overall, clinical stage IV was the most common (57.18%) followed by stage III (24.55%), stage II (13.77%) and stage I (4.49%). Conclusion: Oral cancers are diagnosed late (Stage III and IV) in Pakistan and need immediate public and professional attention. Keywords: Oral Cancer, Clinical Staging, TNM Staging